Penerapan User Centered Design pada Perancangan Ulang Aplikasi Starbucks Indonesia - Merdyanti, Decindy; Defriani, Meriska; Nugroho, Imam Maruf (STMIK Banjarbaru, 2023)
Starbucks Indonesia, currently developing business idea through a mobile application. However, Starbucks Indonesia still faces some weaknesses in providing a comfortable user experience with its application. This research aims to improve the user interface and user experience of the Starbucks Indonesia application and measure the level of user experience with the services provided by the application, as well as provide solutions to the issues users face. The research follows the User-Centered Design method, The testing methods employed are User Experience Questionnaire and Concurrent Think Aloud method. The results of the UEQ testing indicate that the benchmark scores of the UEQ questionnaire for evaluating the new design excel in aspects of attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty, receiving an excellent rating compared to the benchmark scores of the UEQ questionnaire for evaluating the old design. Concurrent Think Aloud testing revealed users felt the redesign provided a better experience.Keywords: Redesign; Starbucks Indonesia; User Centered Design; User Experience Questionnaire; Concurrent Think AloudÂ AbstrakStarbucks Indonesia sedang mengembangkan ide bisnisnya dalam aplikasi mobile yaitu Starbucks Indonesia, namun Starbucks Indonesia tetap menghadapi kelemahan dalam membuat penggunanya nyaman ketika menggunakan aplikasi Starbucks Indonesia. Tujuan pada penelitian ini adalah untuk menghasilkan hasil perbaikan user interface dan user experience pada aplikasi Starbucks Indonesia. Lalu tujuan penelitian juga untuk mengukur tingkat user experience terhadap layanan yang diberikan oleh aplikasi Starbucks Indonesia dan membuat solusi dari masalah yang pengguna rasakan. Tahapan penelitian ini menggunakan metode User Centered Design, adapun metode pengujian dilakukan dengan metode User Experience Questionnaire dan Concurrent Think Aloud. Hasil pengujian UEQ menunjukkan bahwa nilai benchmark kuesioner UEQ evaluasi desain baru pada aspek attractiveness, perspicuity, efficiency, dependability, stimulation, dan novelty mendapat nilai excellent dibandingkan dengan nilai benchmark kuesioner UEQ evaluasi desain lama. Lalu pada pengujian Concurrent Think Aloud evaluasi desain baru didapat hasil bahwa pengguna merasa adanya perancangan ulang ini telah memberikan pengalaman yang lebih baik bagi pengguna.Kata Kunci: Perancangan Ulang; Starbucks Indonesia; User Centered Design; User Experience Questionnaire; Concurrent Think Aloud